In Harm's Way? Infrastructure Investments and the Persistence of Coastal Cities - Balboni, Clare (American Economic Review, 2025)
Coasts contain a disproportionate share of the world's population, reflecting historical advantages, but environmental change threatens a reversal of coastal fortune in the coming decades as natural disasters intensify and sea levels rise. This paper considers whether large infrastructure investments should continue to favor coastal areas. I estimate a dynamic spatial equilibrium framework using detailed geo-referenced data on road investments in Vietnam from 2000 to 2010 and find evidence that coastal favoritism has significant costs. The results highlight the importance of accounting for the dynamic effects of environmental change in deciding where to allocate infrastructure today. (JEL H54, O18, P25, Q54, R11, R42, R58)